Pathogenesis and treatment of renal failure in multiple myeloma - Dimopoulos, M.A.; Kastritis, E.; Rosinol, L.; Bladé, J.; Ludwig, H. (Leukemia, 2008)
Renal failure is a frequent complication in patients with multiple myeloma (MM) that causes significant morbidity. In the majority of cases, renal impairment is caused by the accumulation and precipitation of light chains, which form casts in the distal tubules, resulting in renal obstruction. In addition, myeloma light chains are also directly toxic on proximal renal tubules, further adding to renal dysfunction. Adequate hydration, correction of hypercalcemia and hyperuricemia and antimyeloma therapy should be initiated promptly. Recovery of renal function has been reported in a significant proportion of patients treated with conventional chemotherapy, especially when high-dose dexamethasone is also used. Severe renal impairment and large amount of proteinuria are associated with a lower probability of renal recovery. Novel agents, such as thalidomide, bortezomib and lenalidomide, have significant activity in pretreated and untreated MM patients. Although there is limited experience with thalidomide and lenalidomide in patients with renal failure, data suggest that bortezomib may be beneficial in this population. Clinical studies that have included newly diagnosed and refractory patients indicate that bortezomib-based regimens may result in rapid reversal of renal failure in up to 50% of patients and that full doses of bortezomib can be administered without additional toxicity.